Risk of impaired cerebellar growth in preterm infants: a prospective mastoid fontanelle ultrasound study - Flavia Correa; Manuel Cunha; Rosalina Barroso; Helena Carreiro (Hygeia Press di Corridori Marinella, 2014)
Objectives: Recent studies realized with magnetic resonance imaging (MRI) showed impaired cerebellar growth in follow-up of preterm infants. Cerebellar injury may contribute to impaired motor, cognitive, language and behavioral dysfunction seen among this group. This study was designed to evaluate cerebellar growth in premature babies by ultrasound, a bedside imaging method, and to detect variables that could influence impaired cerebellar growth. Material and methods: Postnatal cerebellar growth, measured by transverse cerebellar diameter (TCD), was prospectively assessed in 88 consecutive preterm infants born ≤ 32 weeks of gestational age (GA). TCD was obtained via mastoid fontanelle (MF) ultrasound on a weekly basis, since the first week of life until 40 weeks postmenstrual age (p.m.a.). Variables that could influence cerebellar growth, such as GA, intrauterine growth restriction (IUGR), periventricular leukomalacia (PVL), peri-intraventricular hemorrhage (IVH), and posterior fossa hemorrhage (PFH) were evaluated. Results: TCD could be measured by MF ultrasound in all patients. Cerebellar growth occurred linearly with postnatal age. At 40th p.m.a. week, TCD was smaller in IUGR group compared with no IUGR infants but their weekly cerebellar growth was similar. At term-equivalent age, cerebellar size was influenced by PFH, PVL and IVH severity. Conclusion: TCD measured by MF ultrasound has demonstrated to be a bedside method for measuring the cerebellum in preterm babies. Impaired cerebellar growth seemed to be influenced by other brain lesions in these patients. We suggest that cerebellum should be studied in preterm infants born ≤ 32 weeks gestation, at term equivalent age, using MF ultrasound.